Mini-gaps and novel giant negative magnetoresistance in InAs/GaSb semimetallic superlattices - Lakrimi, M; Khym, S; Symons, D; Nicholas, R; Peeters, F; Mason, N; Walker, P (1998)
We have studied the temperature dependence of the magnetoresistance of semimetallic InAs/GaSb structures with magnetic field applied parallel to the layers. We present the first unambiguous evidence for the presence of a mini-gap at the crossing point between the electron and hole dispersion relations. The resistivity is found to change from semiconductor-like behaviour with a strong temperature dependence at low parallel magnetic fields to that of a semimetal with a weak temperature dependence at high field. Furthermore, the magnetoresistance, for intrinsic samples, is found to decrease with field by as much as 70% at low temperatures. As the parallel magnetic field is increased the centres of the electron and hole dispersions are shifted apart in k-space and at sufficiently high field the mini-gap is destroyed and the bands overlap fully. Finally, a theoretical model allows us to estimate that the mini-gap is of order 7 meV. (C) 1998 Elsevier Science B.V. All rights reserved.